Application of Think Explain Apply Learning Strategies to Elementary Age Students - Nurul Sakinah (Journal of Contemporary Gender and Child Studies, 2023)
We often encounter learning in children by playing, when carrying out the learning process, the teacher always uses learning strategies in the classroom. The learning strategy is the method chosen by the teacher in the learning process which can provide convenience and facilities for students towards achieving learning goals. In this study, researchers used the Think-Explain-Apply learning strategy. Think means to think, Explain means to explain, and Apply means to apply. This type of research is a qualitative research. Qualitative research is research that involves verbal data and is analyzed inductively in the form of narratives, schemes and pictures. This research was conducted at the MIS Maura El-Mumtaz school on Saturday, March 4 2023. The object of this research was the implementation of learning using the Think-Explain-Apply method for fifth grade students. The data collection techniques used in this study were observation, documentation, and interview. Observations made by observing events, motion, and processes during learning takes place. As for the results of research regarding the application of this strategy to fifth grade students, namely being able to train and improve children's thinking skills and be able to solve problems according to their abilities.